18F-FDG PET-CT for Staging of Conjunctival Melanoma - Damian, Andres; Gaudiano, Javier; Engler, Henry; Alonso, Omar (World Journal of Nuclear Medicine, 2013)
The value of F-18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET-CT) for the evaluation of cutaneous melanoma has been demonstrated previously. However, there are few reports regarding the use PET-CT for the staging of conjunctival melanoma (CM). We report here a case, a 34-year-old male with a six-month history of a pigmented nodule at the palpebral conjunctiva of the left eye, and a firm left preauricular lymph node detected on physical examination. Biopsy of the ocular lesion confirmed CM, and fine needle aspiration cytology of the preauricular node was positive for malignancy. CT showed three pulmonary nodules. An 18F-FDG PET-CT was performed to restage the patient. The study showed hypermetabolic lesions in the left eye, and in the left preauricular node. The scan was negative for metastasis. These findings were important in guiding management of the disease in this patient. Future prospective studies should further evaluate the role of 18F-FDG PET-CT for the staging of CM.
Keywords: Conjunctival melanoma; F-18 fluorodeoxyglucose positron emission tomography/computed tomography; positron emission tomography